Analysis of Work Readiness Among Management Students of the 2021 Cohort at Pembangunan Nasional Veteran Jawa Timur University - Dwi Ayu Saraswati; Sulastri Irbayuni (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze the influence of interpersonal skills (soft skills) and practical skills (hands-on skills) on the work readiness of students at the Faculty of Economics and Business, Universitas Pembangunan Nasional “Veteran” East Java in the 2021 academic year. The approach used was quantitative with a survey method through the distribution of questionnaires to 79 respondents. The collected data were analyzed using the Partial Least Squares (PLS) technique. The results of the study indicate that both interpersonal skills and practical skills play an important role in improving students' work ability or work readiness. This finding confirms that mastery of two types of skills, namely technical skills (technical skills) and non-technical skills (non-technical skills), is essential for students to be able to adapt and compete in the world of work. Thus, educational institutions are expected to balance the development of academic aspects and practical skills to prepare graduates who are ready to face professional challenges.